An Assessment of the Malabo Protocol on Impunity in Africa. - Tsibo, B.K. (University of Ghana, 2018)
In June 2014, the AU Assembly of Heads of State and Government meeting in Malabo, Equatorial Guinea adopted the Protocol on Amendments to the Protocol on the Statute of the African Court of Justice and Human Rights (the Malabo Protocol) and called on AU Member States to sign and ratify it. The study examined the potential effect the Malabo Protocol will have on the fight against impunity in Africa. The study further examined the relevance of the unaccustomed ‘international’ crimes stipulated in the Malabo Protocol which seeks to establish an international criminal tribunal. To investigate these issues, qualitative research method was employed in the assessment of the Protocol. The theory of neo-institutionalism serves as the theoretical framework for this work. A semi-structured interview guide was used to elicit responses from experts. Several sources of secondary data were also used. The study found that, the Malabo Protocol cannot constitute a better instrument to judge and prosecute the authors of the most serious crimes of international concern regardless of the AU’s claim that the African Court of Justice and Human Rights (ACJHR) is aimed at fighting impunity in Africa. The study recommended among others that future amendment of the Malabo Protocol should get rid of the immunity provision contained in the Protocol.
MA.
Keywords: Malabo Protocol; Africa; Equatorial Guinea